Strategy of Action to Understand Corruption in Minors - Dwi Ananda; Matang Matang (Jurnal Edukasi Terkini, 2026)
Purpose-This article aims to identify and develop effective strategies in providing an understanding of corruption to underage teenagers. With this effort, it is hoped that the younger generation can play an active role in creating a clean and corruption-free society in the future. Research. Methodology / Design / Approach-This study uses a qualitative method with a literature study approach. This method was chosen to provide a comprehensive overview and in-depth understanding of the strategy for understanding corruption in underage teenagers, as well as to generate new insights into the use of digital technology in anti-corruption education. Findings-Anti-corruption education programs that use participatory and interactive methods, such as case simulations, group discussions, and role-playing, have proven effective in increasing adolescent awareness of corruption and its impacts. Social media also plays a significant role in spreading anti-corruption messages through interesting educational content. However, obstacles from the environment such as the permissive attitude of family and friends are still challenges that need to be overcome. Family and community involvement is essential to strengthen the impact of anti-corruption education. Originality / Value-This article makes an important contribution by combining an interactive education approach and the use of social media as an innovative strategy in building an anti-corruption culture from an early age. This approach emphasizes the importance of collaboration between schools, families, communities, and digital technologies to create sustainable behavioral change in adolescents.